Simple and reliable method to simultaneously determine urinary 1‐ and 2‐naphthol using in situ derivatization and gas chromatography‐mass spectrometry for biological monitoring of naphthalene exposure in occupational health practice. Issue 1 (26th July 2020) - Takeuchi, Akito; Nakamura, Sadao; Namera, Akira; Kondo, Tomoaki; Onuki, Hiroyuki; Yamamoto, Shinobu; Okamura, Shingo; Nishinoiri, Osamu; Endo, Yoko; Miyauchi, Hiroyuki; Endo, Ginji
Abstract: Objectives: The aim of this study was to develop and validate a simple and reliable gas chromatography‐mass spectrometry (GC‐MS) method to simultaneously determine urinary 1‐naphthol (1‐NAP) and 2‐naphthol (2‐NAP) for biological monitoring of occupational exposure to naphthalene. Methods: NAPs were derivatized in situ with acetic anhydride after enzymatic hydrolysis, extracted with n ‐hexane, and analyzed using GC‐MS. Validation of the proposed method was conducted in accordance with US Food and Drug Administration guidance. A final validation was performed by analyzing a ClinChek ® ‐Control for phenolic compounds. Results: The linearity of calibration curves was indicated by a high correlation coefficient (>0.999) in the concentration range 1‐100 μg/L for each NAP. The limits of detection and quantification for each NAP were 0.30 and 1.00 μg/L, respectively. The recovery was 90.8%‐98.1%. The intraday and interday accuracies, expressed as the deviation from the nominal value, were 92.2%‐99.9% and 93.4%‐99.9%, respectively. The intraday and interday precision, expressed as the relative standard deviation, was 0.3%‐3.9% and 0.4%‐4.1%, respectively. The ClinChek ® values obtained using our method were sufficiently accurate. Conclusions: The proposed method is simple, reliable, and appropriate for routine analyses, and is useful for biological monitoring of naphthalene exposure in occupational health practice.